2018
DOI: 10.3892/mmr.2018.8884
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine on the metabolism and gene expression profile of Sprague‑Dawley rat primary osteoblasts

Abstract: Smoking is a risk factor associated with bone and oral diseases, particularly periodontitis. Nicotine, the major toxic component of tobacco, is able to affect the quality and quantity of bone. Osteoblasts serve an important role in bone formation. Thus far, the effects of nicotine on metabolism-associated gene and protein expression in osteoblasts have been controversial and the mechanisms remain unclear. The present study assessed alterations in osteogenic activity by performing a Cell Counting kit-8 assay to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…Primary OBs were isolated from the skulls of newly born (72 h) SD rats. The standardized extraction procedure of primary OBs was carried as previously described [21, 22]. The cells were collected and dissolved in DME/F-12 1:1 culture medium (HyClone) supplemented with 10% foetal bovine serum (Excel), penicillin-streptomycin mixed liquor (Solarbio) and incubated in a humidified atmosphere of 95% air and 5% CO2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Primary OBs were isolated from the skulls of newly born (72 h) SD rats. The standardized extraction procedure of primary OBs was carried as previously described [21, 22]. The cells were collected and dissolved in DME/F-12 1:1 culture medium (HyClone) supplemented with 10% foetal bovine serum (Excel), penicillin-streptomycin mixed liquor (Solarbio) and incubated in a humidified atmosphere of 95% air and 5% CO2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Although smoking has effects on multiple biological systems that may predispose to chronic periodontitis—including amplification of cholinergic anti‐inflammatory signaling, a reduced antibody response, suppressed immune cell function, promotion of osteoclast/osteoblast imbalance, a depleted antioxidant defense, and compromised tissue remodeling—this review will focus specifically on the vascular response itself.…”
Section: Periodontal Diseases and Cigarette Smokingmentioning
confidence: 99%
“…In vitro studies showed that one of the major components of cigarette smoke, nicotine, decreased the formation of osteoblasts from human bone marrow mesenchymal stem cells [88]. Another study demonstrated that proliferation and formation of mineralized nodules were reduced in rat primary osteoblasts [89]. Gene expression analysis on these cells revealed two pathways related to bone metabolism affected by nicotine, i.e., Hedgehog and Notch pathways [89].…”
Section: Effects Of T3 On Bone Loss Due To Cigarette-smokingmentioning
confidence: 99%
“…Another study demonstrated that proliferation and formation of mineralized nodules were reduced in rat primary osteoblasts [89]. Gene expression analysis on these cells revealed two pathways related to bone metabolism affected by nicotine, i.e., Hedgehog and Notch pathways [89]. Other studies found that the effects of nicotine on osteogenesis might be bi-phasic in nature, whereby negative impacts were only observed with high doses [90].…”
Section: Effects Of T3 On Bone Loss Due To Cigarette-smokingmentioning
confidence: 99%